Design and Measurements of a Low-power Low-Date-rate Direct-detection Wireless Receiver with Improved Co-channel Interference Robustness - Abughannam, Saed; Kruse, Stephan; Iftekhar, Mohammed; Scheytt, J. Christoph (German Microwave Conference 2022 (GeMiC 2022))

Fachliche und überfachliche Herausforderungen in der Studieneingangsphase Physik - Bauer, Anna; Woitkowski, David; Reuter, Dirk; Reinhold, Peter (Hochschullehre erforschen.)
Die Studieneingangsphase Physik stellt für die Studienanfänger Innen einen komplexen Lernprozess mit vielfältigen Anforderungen auf fachlicher, Metakognitions- und Sozialisations-Ebene dar, der ihre akademische Identitätsbildung beeinflusst und prägt. Ziel des Projektes Paderborner Studieneingangsphase Physik (PSΦ) ist die evidenzbasierte Gestaltung eines strukturierten Studieneinstiegs und einer in sich kohärent abgestimmten Studieneingangsphase „aus einem Guss“. Die Implementation eines neuen Übungsformats (Präsenzübungen) in den Fachvorlesungen sowie die Unterstützung der Studierenden im Bereich des selbstregulierten Lernens zeigen positive Effekte in einer erhöhten Teilnahmequote sowie Zufriedenheit der Studierenden mit der Veranstaltung, in einem aktiveren Arbeitsverhalten sowie einer höheren Bestehensquote der Klausur. Ein messbar größerer Fachwissenserwerb konnte nicht nachgewiesen werden. Auf Basis der Evidenzen konnten Stellschrauben für die Weiterentwicklung sowie für die Unterstützung der Lehrenden abgeleitet werden. In dem Beitrag werden die Gelingensbedingungen und Strukturen für eine wirksame Zusammenarbeit von Fachdidaktik und Fachwissenschaft am Beispiel der Überarbeitung der Studieneingangsphase im Rahmen einer community of practice sowie der Wirksamkeit der Implementierung diskutiert.

Capacity investments in a competitive energy market - Block, Lukas; Westbrock, Bastian
We study the abilities of competitive markets to produce sufficient energy capacities to meet a fixed energy demand. Renewable energy producers with stochastic outputs and no variable costs compete against conventional energy producers with deterministic, pollutant outputs and increasing marginal costs. We find that either market forces are strong enough to serve the entire demand, or they are too weak such that the market fails and nothing is produced. This crucially depends on the relative cost of renewable energy investments, such that relatively cheap renewable energy causes the market to fail. Welfare analyses show that with increasing levels of conventional energy pollution the ability of the market to produce an ecient outcome further declines. As a policy implication, our findings refute the use of a strategic reserve as a blackout backstop solution. Instead, a capacity mechanism consisting of a tax-and-subsidy scheme can align the market outcome with the eficient solution for all pollution levels and relative costs of renewable energy capacities.
Keywords: Renewable versus conventional energy; capacity mechanisms; strategic reserves; capacity payments

Designing a GIS-AHP-Based Spatial Decision Support System for Discovering and Visualizing Suitable Locations for Electric Vehicle Charging Stations - Priefer, Jennifer; Steiger, Lennart (Wirtschaftsinformatik 2022 Proceedings)

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, A.; Grydin, O.; Schaper, M. (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Development and Evaluation of a Collaborative Stock Trading Environment in Virtual Reality - Yigitbas, Enes; Gottschalk, Sebastian; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
Due to the proliferation of Virtual Reality (VR) technology, VR is finding new applications in various domains, such as stock trading. Here, traders invest in stocks intending to increase their profit. For this purpose, in conventional stock trading, traders usually make use of 2D applications on desktop or laptop devices. This leads to many drawbacks such as poor visibility due to limited 2D representation, complex interaction due to indirect interaction via mouse and keyboard, or restricted support for collaboration between traders. To overcome these issues, we have developed a novel collaborative, virtual environment for stock trading, which enables stock traders to view financial information and trade stocks with other collaborators. The main results of a usability study indicate that the VR environment, compared to conventional stock trading, shows no significant advantages concerning efficiency and effectiveness, however, we could observe an increased user satisfaction and better collaboration.
Keywords: virtual reality; stock trading; collaboration; usability

A Discrete and Continuous Study of the Max-Chain-Formation Problem - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Information and Computation)
Keywords: Computational Theory and Mathematics; Computer Science Applications; Information Systems; Theoretical Computer Science

Semi-automatic Integrated Safety and Security Analysis for Automotive Systems - Fockel, Markus; Schubert, David; Trentinaglia, Roman; Schulz, Hannes; Kirmair, Wolfgang (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Integrating Security Protocols in Scenario-based Requirements Specifications - Koch, Thorsten; Trippel, Sascha; Dziwok, Stefan; Bodden, Eric (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen.Gänge.Zwischen.Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Methodenentwicklung zur Versagensanalyse aufgrund der Aushärtung vorgeschädigter Klebverbindungen in stahlintensiven Mischbaustrukturen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Nagel, Christof; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Funnel control of linear systems under output measurement losses - Lanza, Lukas Johannes; Berger, Thomas

Network and Service Coordination: Conventional and Machine Learning Approaches" - Schneider, Stefan Balthasar

A Reference Process Model for Usage Data-Driven Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 55th Hawaii International Conference on System Sciences)
Cyber-physical systems generate and collect huge amounts of usage data during operation. Analyzing these data may enable manufacturing companies to identify weaknesses and learn about the users of their products. Such insights are valuable in the early phases of product development like product planning, as they facilitate decision-making for product improvement. The analysis and exploitation of usage data in product planning, however, is a new task for manufacturing companies. To reduce mistakes and improve the results, companies should build upon a suitable reference process model. Unfortunately, established models for analyzing data cannot be easily applied for product planning. In this paper, we propose a reference process model for usage data-driven product planning. It builds on three well-established models for analyzing data and addresses the unique characteristics of usage data-driven product planning. Finally, we customize the model for a manufacturing company and demonstrate how it could be implemented in practice.

Enhancing Human-in-the-Loop Adaptive Systems through Digital Twins and VR Interfaces - Yigitbas, Enes; Karakaya, Kadiray; Jovanovikj, Ivan; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Collaborative Software Modeling in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Search Space Characterization for Approximate Logic Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Reuter, Lucas David; Platzner, Marco (2022 59th ACM/IEEE Design Automation Conference (DAC))

MUSCAT: MUS-based Circuit Approximation Technique - Witschen, Linus Matthias; Wiersema, Tobias; Artmann, Matthias; Platzner, Marco (Design, Automation and Test in Europe (DATE))

Exact output tracking in prescribed finite time via funnel control - Lanza, Lukas Johannes
We extend a recent result in high-gain feedback output tracking control to achieve exact tracking within finite time, i.e., the output of a system and its relevant derivatives have certain exact values at a predefined finite time. We propose a new funnel control scheme achieving this, whereas the error between the reference and the output evolves within prescribed bounds. Applications of this are, for instance, linking up two parts of a train, or docking spaceships.

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse des Versagensverhaltens geklebter Stahl-Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

High-Bandwidth Arbitrary Signal Detection Using Low-Speed Electronics - Meier, Janosch; Singh, Karanveer; Misra, Arijit; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (IEEE Photonics Journal)
The growing demand for bandwidth and energy efficiency requires new solutions for signal detection and processing. We demonstrate a concept for high-bandwidth signal detection with low-speed photodetectors and electronics. The method is based on the parallel optical sampling of a high-bandwidth signal with sinc-pulse sequences provided by a Mach-Zehnder modulator. For the electronic detection and processing this parallel sampling enables to divide the high-bandwidth optical signal with the bandwidth B into N electrical signals with the baseband bandwidth of B/(2N) . In proof-of-concept experiments with N=3 , we present the detection of 24 GHz optical signals by detectors with a bandwidth of only 4 GHz. For ideal components, the sampling and bandwidth down-conversion does not add an excess error to the signals and even for the non-ideal components of our proof-of-concept setup, it is below 1%. Thus, the rms error for the measurement of the 24 GHz signal was reduced by a factor of about 3.4 and the effective number of bits were increased by 1.8.

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

Methodenentwicklung für die Simulation mechanischer Fügeprozesse mit besonderer Berücksichtigung fügespezifischer Reibverhältnisse - Rossel, Moritz Sebastian; Meschut, Gerson

Evaluation of Algorithms for the Node Capacitated Clique - Roopa, Rajanna

A Versatile Metasurface Enabling Superwettability for Self‐Cleaning and Dynamic Color Response - Lu, Jinlong; Sain, Basudeb; Georgi, Philip; Protte, Maximilian; Bartley, Tim; Zentgraf, Thomas (Advanced Optical Materials)
Metasurfaces provide applications for a variety of flat elements and devices due to the ability to modulate light with subwavelength structures. The working principle meanwhile gives rise to the crucial problem and challenge to protect the metasurface from dust or clean the unavoidable contaminants during daily usage. Here, taking advantage of the intelligent bioinspired surfaces which exhibit self-cleaning properties, a versatile dielectric metasurface benefiting from the obtained superhydrophilic or quasi-superhydrophobic states is shown. The design is realized by embedding the metasurface inside a large area of wettability supporting structures, which is highly efficient in fabrication, and achieves both optical and wettability functionality at the same time. The superhydrophilic state enables an enhanced optical response with water, while the quasi-superhydrophobic state imparts the fragile antennas an ability to self-clean dust contamination. Furthermore, the metasurface can be easily switched and repeated between these two wettability or functional states by appropriate treatments in a repeatable way, without degrading the optical performance. The proposed design strategy will bring new opportunities to smart metasurfaces with improved optical performance, versatility, and physical stability.

Aufarbeitung und lmplementierung von DAG-Rider - Korzeczek, Sebastian

Hybrid Routing in Three Dimensions - Nachtigall, Marcel

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Experimentelle und numerische Untersuchung des Einflusses variabler Betriebstemperaturen auf das Trag- und Versagensverhalten struktureller Klebverbindungen unter Crashbelastung - Striewe, Marius; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar; Steinmann, Paul (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Reproducibility in Polymer Laser Sintering - Klippstein, Sven Helge

mobile-env: An Open Platform for Reinforcement Learning in Wireless Mobile Networks - Schneider, Stefan Balthasar; Werner, Stefan; Khalili, Ramin; Hecker, Artur; Karl, Holger (IEEE/IFIP Network Operations and Management Symposium (NOMS))
Recent reinforcement learning approaches for continuous control in wireless mobile networks have shown impressive results. But due to the lack of open and compatible simulators, authors typically create their own simulation environments for training and evaluation. This is cumbersome and time-consuming for authors and limits reproducibility and comparability, ultimately impeding progress in the field. To this end, we propose mobile-env, a simple and open platform for training, evaluating, and comparing reinforcement learning and conventional approaches for continuous control in mobile wireless networks. mobile-env is lightweight and implements the common OpenAI Gym interface and additional wrappers, which allows connecting virtually any single-agent or multi-agent reinforcement learning framework to the environment. While mobile-env provides sensible default values and can be used out of the box, it also has many configuration options and is easy to extend. We therefore believe mobile-env to be a valuable platform for driving meaningful progress in autonomous coordination of wireless mobile networks.
Keywords: wireless mobile networks; network management; continuous control; cognitive networks; autonomous coordination; reinforcement learning; gym environment; simulation; open source

Governance and Reputation in the Market for Experience Goods - Fanasch, Patrizia

Research Approaches on Workplace Learning
The volume comprises a variety of research approaches that seek to explore and understand employees’ learning and development through and for work. Working life reveals challenges through technological, economic and societal development that can only rudimentarily be addressed by formal education and training. Workplace learning becomes more and more important for employees and enterprises to successfully cope with these challenges. Workplace learning is a steadily growing field of educational research but it lacks so far a scholastic canon – there is rather a diversity of research approaches. This volume reflects this diversity by bringing together researchers from different countries and different theoretical backgrounds, presenting their current research on topics that all are relevant for understanding presages, processes and outcomes of workplace learning. Hence, this volume is of relevance for researchers as well as practitioners in the field and policy makers.
Keywords: tivesTeam learningTeam climateSocial influences on team learningKnowledge construction in teamsLearning cultureAcknowledgement of competencesTechnology and professional learningCreation of a learning eco-systemDiversity as a challenge for organisationsHigher education as preparation for WPLSocial support in networks and professional learningvocational and professional education

ROM-Based Multiobjective Optimization of Elliptic PDEs via Numerical Continuation - Banholzer, Stefan; Gebken, Bennet; Dellnitz, Michael; Peitz, Sebastian; Volkwein, Stefan (Non-Smooth and Complementarity-Based Distributed Parameter Systems)
Multiobjective optimization plays an increasingly important role in modern applications, where several objectives are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. Since the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging which is particularly problematic when the objectives are costly to evaluate as is the case for models governed by partial differential equations (PDEs). To decrease the numerical effort to an affordable amount, surrogate models can be used to replace the expensive PDE evaluations. Existing multiobjective optimization methods using model reduction are limited either to low parameter dimensions or to few (ideally two) objectives. In this article, we present a combination of the reduced basis model reduction method with a continuation approach using inexact gradients. The resulting approach can handle an arbitrary number of objectives while yielding a significant reduction in computing time.

Efficient Virtual Design and Testing of Autonomous Vehicles - Peitz, Sebastian; Dellnitz, Michael; Bannenberg, Sebastian (German Success Stories in Industrial Mathematics)
With the ever increasing capabilities of sensors and controllers, autonomous driving is quickly becoming a reality. This disruptive change in the automotive industry poses major challenges for manufacturers as well as suppliers as entirely new design and testing strategies have to be developed to remain competitive. Most importantly, the complexity of autonomously driving vehicles in a complex, uncertain, and safety-critical environment requires new testing procedures to cover the almost infinite range of potential scenarios.

Agency: Taking Stock of Workplace Learning Research - Goller, Michael; Paloniemi, Susanna (Research Approaches on Workplace Learning)
This chapter presents a discussion of the concept of agency. Agency is understood as a multifaceted construct describing the idea that human beings make choices, act on these choices, and thereby exercise influence on their own lives as well as their environment. We argue that the concept is discussed from three different perspectives in the literature—transformational, dispositional, and relational—that are each related to learning and development in work contexts. These perspectives do not reflect incompatible positions but rather different aspects of the same phenomena. The chapter also offers an avenue of insight into empirical studies that employ agency as a central concept as well as discussions about concepts that closely overlap with ideas of human beings as agents of power and influence.
Keywords: Agency Workplace learning Professional development Proactivity Self-direction

Research on Workplace Learning in Times of Digitalisation - Harteis, Christian (Research Approaches on Workplace Learning)
The article explores the particular quality of changes introduced through the latest wave of digital transformation of workplaces. It has effects on workflow processes, on distribution of work and tasks, and the mode of distributing working tasks, e.g. through cyber-physical systems. Hence, the changes in work are manifold and require changes in vocational education and training as well as in workplace learning. These changes reveal new challenges for research on workplace learning. Finally, conclusions for future workplace learning research will be developed.
Keywords: Digitalisation Self organisation Distribution of labour Automation

From Agile Strategic Foresight to Sustainable Mechatronic and Cyber-Physical Systems in Circular Economies - Gräßler, Iris; Pottebaum, Jens (Design Methodology for Future Products)

Compensation of LF Common-Mode Noise by the internal DC/DC-Stage for transformerless On-Board Chargers at Three- and Single-Phase Operation - Schafmeister, Frank (International Conference on Electric & Electronic in Hybrid and Electric Vehicles and Electric Energy Management (EEHE),)

An Open-Source Transistor Database and Toolbox as an Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (Proc. 37th IEEE Applied Power Electronics Conference (APEC))

Robust Hysteresis Control for LLC Resonant Converters Using a Fully Isolated Measurement Scheme - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Second Harmonic Optical Circular Dichroism of Plasmonic Chiral Helicoid-III Nanoparticles - Spreyer, Florian; Mun, Jungho; Kim, Hyeohn; Kim, Ryeong Myeong; Nam, Ki Tae; Rho, Junsuk; Zentgraf, Thomas (ACS Photonics)
While plasmonic particles can provide optical resonances in a wide spectral range from the lower visible up to the near-infrared, often, symmetry effects are utilized to obtain particular optical responses. By breaking certain spatial symmetries, chiral structures arise and provide robust chiroptical responses to these plasmonic resonances. Here, we observe strong chiroptical responses in the linear and nonlinear optical regime for chiral L-handed helicoid-III nanoparticles and quantify them by means of an asymmetric factor, the so-called g-factor. We calculate the linear optical g-factors for two distinct chiroptical resonances to −0.12 and –0.43 and the nonlinear optical g-factors to −1.45 and −1.63. The results demonstrate that the chirality of the helicoid-III nanoparticles is strongly enhanced in the nonlinear regime.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Biotechnology; Electronic; Optical and Magnetic Materials

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, D.; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, K. D.; Reuter, D.; Schumacher, S.; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Anonymity and Self-Expression in Online Rating Systems - An Experimental Analysis - Hoyer, Britta; van Straaten, Dirk (Journal of Behavioral and Experimental Economics)
Keywords: General Social Sciences; Economics and Econometrics; Applied Psychology

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Resonant evanescent excitation of OAM modes in a high-contrast circular step-index fiber - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Complex Light and Optical Forces XVI)
Resonant evanescent coupling can be utilized to selectively excite orbital angular momentum (OAM) modes of high angular order supported by a thin circular dielectric rod. Our 2.5-D hybrid-analytical coupled mode model combines the vectorial fields associated with the fundamental TE- and TM-modes of a standard silicon photonics slab waveguide, propagating at oblique angles with respect to the rod axis, and the hybrid modes supported by the rod. One observes an efficient resonant interaction in cases where the common axial wavenumber of the waves in the slab matches the propagation constant of one or more modes of the rod. For certain modes of high angular order, the incident wave is able to transfer its directionality to the field in the fiber, exciting effectively only one of a pair of degenerate OAM modes
Keywords: tet_topic_waveguide

Continuous and discrete Noether's fractional conserved quantities for restricted calculus of variations - Cresson, Jacky; Jiménez, Fernando; Ober-Blöbaum, Sina (AIMS)